2020
DOI: 10.3390/ht9020012
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota and Human Reproduction: The Case of Female Infertility

Abstract: During the last decade, the availability of next-generation sequencing-based approaches has revealed the presence of microbial communities in almost all the human body, including the reproductive tract. As for other body sites, this resident microbiota has been involved in the maintenance of a healthy status. As a consequence, alterations due to internal or external factors may lead to microbial dysbiosis and to the development of pathologies. Female reproductive microbiota has also been suggested to affect in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 102 publications
2
49
0
5
Order By: Relevance
“…Our study has some limitations. First, the microbiota of the genitourinary tract of the partner was not evaluated and some studies have shown that male microbiota may also play a fundamental role in reproductive outcomes [132,133]. In fact, the couple (when applicable) should be considered as a single entity to achieve the best reproductive outcomes [134].…”
Section: Discussionmentioning
confidence: 99%
“…Our study has some limitations. First, the microbiota of the genitourinary tract of the partner was not evaluated and some studies have shown that male microbiota may also play a fundamental role in reproductive outcomes [132,133]. In fact, the couple (when applicable) should be considered as a single entity to achieve the best reproductive outcomes [134].…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, a role of the microbiota in human reproduction has emerged [ 71 , 72 ]. In particular, the semen microbiota composition has been related to altered sperm cells motility, hyperviscosity, oligoasthenoteratozoospermia, and/or sperm DNA fragmentation [ 73 , 74 , 75 ].…”
Section: Intrinsic Factorsmentioning
confidence: 99%
“… Individual variability factors affecting semen microbiota composition and processes in which semen microbiota has been suggested to play a role [ 12 , 19 , 21 , 23 , 36 , 49 , 55 , 56 , 57 , 58 , 63 ]. The simultaneous evaluation of the female partner’s microbiota should be taken into account considering their mutual influences and the potential effects on couples’ and offspring health [ 64 ]. …”
Section: Figurementioning
confidence: 99%